PENGARUH KUALITAS PELAYANAN STAF PENGAJAR TERHADAP KEPUASAN SISWA PADA LEMBAGA BIMBINGAN BELAJAR SONY SUGEMA COLLEGE BANDUNG - Muhammad Rizal Firdaus, - (2012)
The main concern of this research was decreasing student satisfaction in Sony Sugema College Bandung Course. which is indicated with assurance this student that have not met the company standard. This matters could block the company from its purpose if not soon be overcome. The Aim of this research is to depict the quality of service of instructor staff, student satisfactian, and the effect of quality of service of instructor staff to student satisfactian in Sony Sugema College Bandung Course. The aspect that analyzed in this research includes two things, there are quality of service of instructor staff and student satisfaction. Eighty employees of student Sony Sugema College Bandung Course were involved as respondents. A descriptive method with Explanatory Survey Method approach was employed. The data were obtained through questionnaire with Likert Scale model and were then analyzed by using simple regression analysis. The results showed that the quality of service of instructor staff and student satisfaction take position in high categories. The result of correlation calculation is 0,456, which indicate a strong correlation between the quality of service of instructor staff and student satisfaction. The calculation result of simple regression analysis shows equation, that is Y = 21,519 + 0,428X and KD = 20,78%, means that the influence the quality of service of instructor staff towards student satisfaction is for 20.78%, while the remaining 79.22% influenced by other factors not examined. The suggestion from this research result is to improve assurance of the student through appropriate service quality of expectation. That thing is doing by realizing all requirement and student desire, in order to obtainable high student satisfaction.